Axial Compressive Performance of Corroded Concrete Columns Strengthened by Alkali-Activated Slag Ferrocement Jackets - Fang, Shuai (Frontiers in Materials, 2020)
Chloride-induced corrosion of reinforcement has endangered the safety of reinforced concrete (RC) structures. It is, therefore, necessary to strengthen the corroded RC members to ensure structural safety. This study aims to investigate the effectiveness of alkali-activated slag (AAS) ferrocement jackets in strengthening corroded RC columns. AAS ferrocement specimens with various layers of stainless steel wire mesh (SSWM) were subjected to direct tensile tests. Square RC columns suffered artificially accelerated corrosion and were subsequently strengthened by AAS ferrocement jackets. Axial compressive tests were conducted on the column specimens. Experimental results have shown that corroded specimens suffer severe losses in loading capacity up to 46% as compared with the control one. Volume fraction of transverse SSWM (ρv) plays primary role in loading capacity and ductility of ferrocement and its confinement on column specimens. Ferrocement with ρv of 0.266% can rehabilitate loading capacity of specimens with corrosion degrees of 8.9% and 18.3% by 37% and 46%, respectively. Corroded specimen strengthened by ferrocement with ρv of 0.532% achieves approximately two times the ductility than the one without strengthening. Ferrocement jackets provide better and uniform confinement to core concrete than new stirrups. Analytical models are proposed to predict tensile strength of AAS ferrocement and loading capacity of specimens strengthened by ferrocement jackets. The prediction is in good agreement with experimental results.